Exploring the solutions to the inherent perils of (the multitude of) guidelines - a focus group study of stakeholders' perceptions - Louise H. K. Blume; Jamiu O. Busari; Nico J. H. W. van Weert; Diana M. J. Delnoij (BMC, 2019)
Abstract Background Hospital boards have the responsibility to ensure compliance of hospital staff with guidelines and other norms, but they have struggled to do so. The current study aims to identify possible solutions that address the whole chain of guideline and norm production, use and enforcement and that could help hospital boards and management cope with norms and guidelines. Methods We performed a qualitative study of three focus groups involving a total of 28 participants. In the third focus group, no new themes emerged, indicating that saturation was achieved. Focus group discussions were audiotaped and transcribed verbatim. Results were coded, and three themes emerged from the results. Thick description with selected key quotes is used to display the items in the result section. Results In the first instance, norm developers, norm enforcers, and norm users acknowledged and reformulated the problem before they suggested solutions. The proposed concrete solutions, such as a clear description of the division of tasks within guidelines, clarity about the purpose of guideline recommendations, a maximum number of quality indicators for hospitals and implementation of an ensuring proper Information Technology (IT) infrastructure. Conclusions This study aimed to find solutions for the problems that hospitals encounter in managing a multitude of norms and guidelines. Participants in this study acknowledged the fact that norms and guidelines have become difficult to manage at the hospital level and four potential solutions were identified. Trial registration The study was retrospectively registered on the 21st of July in 2016 in the Dutch Trial Register as NL4061.